2022
DOI: 10.3389/fnhum.2022.943047
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory movement strategies differentially affect attention allocation and gait parameters in persons with Parkinson’s disease

Abstract: Persons with Parkinson’s disease (PwP) are advised to use compensatory strategies such as external cues or cognitive movement strategies to overcome gait disturbances. It is suggested that external cues involve the processing of sensory stimulation, while cognitive-movement strategies use attention allocation. This study aimed to compare over time changes in attention allocation in PwP between prolonged walking with cognitive movement strategy and external cues; to compare the effect of cognitive movement stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
1
1
1
Order By: Relevance
“…It should be noted that the absence of a metronome effect on gait variables in the current study is contrary to previous studies and reviews that suggested that auditory cues increase gait speed and stride length [5,12,13] and reduce gait variability [44][45][46]. However, several studies reported that auditory cueing did not affect these parameters [47][48][49]. The increase in variability when the light stripes were used was previously explained by the different nature of the cues: Visual cues, which are spatial in nature, mainly seem to influence scaling and amplitude generation during walking, while temporal auditory cues tend to affect the timing of gait and interlimb coordination [5,6].…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that the absence of a metronome effect on gait variables in the current study is contrary to previous studies and reviews that suggested that auditory cues increase gait speed and stride length [5,12,13] and reduce gait variability [44][45][46]. However, several studies reported that auditory cueing did not affect these parameters [47][48][49]. The increase in variability when the light stripes were used was previously explained by the different nature of the cues: Visual cues, which are spatial in nature, mainly seem to influence scaling and amplitude generation during walking, while temporal auditory cues tend to affect the timing of gait and interlimb coordination [5,6].…”
Section: Discussioncontrasting
confidence: 99%
“…Theta activity is associated with a variety of cognitive and attentional processes involving both frontal and posterior cortical regions, including the periodic sampling of unattended visual information and navigation of the sensory environment [ 76 ]. This supports the idea that the PD group requires considerable cognitive and attentional resources for processing environmental information [ 77 ]. Caviness et al hypothesised that the increase in theta power was related to the abnormal diffuse acetylcholine and monoamine pathway projection to broad neocortical areas and intrinsic cortical circuits in PD [ 78 ].…”
Section: Discussionsupporting
confidence: 84%
“…This renders them less practical for ongoing real-time monitoring. More recently, algorithms have been developed to extract real-time markers of attentional processes from single channels, necessitating short measurement times, at the scale of seconds [56,57,58,59 ▪ ,60 ▪ ,61,62 ▪ ,63,64,65 ▪ ,66,67].…”
Section: The Feasibility Of Monitoring Attention In Real-time Even Un...mentioning
confidence: 99%